Low‐Cost Antimony Selenosulfide with Tunable Bandgap for Highly Efficient Solar Cells. Issue 9 (19th December 2022) - Dong, Jiabin; Liu, Huizhen; Cao, Zixiu; Liu, Yue; Bai, Yuxing; Chen, Mohan; Liu, Bei; Wu, Li; Luo, Jingshan; Zhang, Yi; Liu, Shengzhong (Frank)
Abstract: About 10% efficient antimony selenosulfide (Sb2 (S, Se)3 ) solar cell is realized by using selenourea as a hydrothermal raw material to prepare absorber layers. However, tailoring the bandgap of hydrothermal‐based Sb2 (S, Se)3 film to the ideal bandgap (1.3–1.4 eV) using the selenourea for optimal efficiency is still a challenge. Moreover, the expensive selenourea dramatically increases the fabricating cost. Here, a straightforward one‐step hydrothermal method is developed to prepare high‐quality Sb2 (S, Se)3 films using a novel precursor sodium selenosulfate as the selenium source. By tuning the Se/(Se+S) ratio in the hydrothermal precursor solution, a series of high‐quality Sb2 (S, Se)3 films with reduced density of deep defect states and tunable bandgap from 1.31 to 1.71 eV is successfully prepared. Consequently, the best efficiency of 10.05% with a high current density of 26.01 mA cm −2 is achieved in 1.35 eV Sb2 (S, Se)3 solar cells. Compared with the traditional method using selenourea, the production cost for the Sb2 (S, Se)3  devices is reduced by over 80%. In addition, the device exhibits outstanding stability, maintaining more than 93% of the initial power conversion efficiency after 30 days of exposure in the atmosphere without encapsulation. The present work definitely paves a facile and effective way to develop low‐cost and high‐efficiency chalcogenide‐based photovoltaic devices. Abstract : Sodium selenosulfate is used as the selenium source to prepare antimony selenosulfide thin film. This facial method not only enables a remarkable efficiency of 10.05% with an ideal bandgap of 1.35 eV but also greatly reduces the production cost. The fabricated solar cells are with high stability.